2020
DOI: 10.29244/jitkt.v12i2.23454
|View full text |Cite
|
Sign up to set email alerts
|

KEPADATAN DAN POLA PERTUMBUHAN TERIPANG Holothuria scabra, Holothuria atra dan Bohadchia marmorata SERTA ASOSIASINYA DENGAN LAMUN DI PESISIR PULAU AMBON, SAPARUA, OSI DAN MARSEGU, PROVINSI MALUKU

Abstract: Holothuria scabra, Holothuria atra dan Bohadschia marmorata merupakan jenis teripang dengan habitat yang sangat beragam dan umumnya ditemukan dalam jumlah yang dominan dibandingkan jenis lainnya. Penelitian ini bertujuan untuk menganalisis kepadatan dan pola pertumbuhan teripang H. scabra, H. atra dan B. marmorata serta asosiasinya dengan jenis lamun di pesisir Pulau Ambon, Pulau Osi dan Pulau Marsegu. Asosiasi teripang dengan lamun dianalisis dengan menggunakan analisis koresponden (CA). Penelitian dilakukan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(19 reference statements)
1
2
0
3
Order By: Relevance
“…On other regions such as Morela waters in Maluku Province (Ongkers et al, 2018) and in Sri Lanka respectively found the similar results (Gamage et al, 2021;Veronika et al, 2018). The negative allometric growth of B. marmorata is in accordance with that of found by Luhulima et al, (2020) Negative allometric growth patterns are often found in other sea cucumber species from the genus Holothuria (Ahmed et al, 2018;Veronika et al, 2018;Aydin, 2020), Sticophus cf. monotuberculatus (Gray et al, 2023).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…On other regions such as Morela waters in Maluku Province (Ongkers et al, 2018) and in Sri Lanka respectively found the similar results (Gamage et al, 2021;Veronika et al, 2018). The negative allometric growth of B. marmorata is in accordance with that of found by Luhulima et al, (2020) Negative allometric growth patterns are often found in other sea cucumber species from the genus Holothuria (Ahmed et al, 2018;Veronika et al, 2018;Aydin, 2020), Sticophus cf. monotuberculatus (Gray et al, 2023).…”
Section: Resultssupporting
confidence: 85%
“…A graph of the length-weight relationship showing the differences in growth patterns of the three species on the two islands is distinctly shown in Figure 2 and 3. Negative allometric growth of the H. atra was also found in the waters of Karimunjawa (Panuluh et al, 2019), in the waters of Panjang Island (Jepara) (Permata et al, 2021), in the waters of Ambon, Saparua, Osi and Marsegu Islands, Maluku Province as well (Luhulima et al, 2020). On other regions such as Morela waters in Maluku Province (Ongkers et al, 2018) and in Sri Lanka respectively found the similar results (Gamage et al, 2021;Veronika et al, 2018).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Derajat keasaman merupakan salah satu parameter lingkungan yang mempengaruhi pertumbuhan teripang pasir. Pertumbuhan teripang pasir juga dipengaruhi oleh pH perairan (Luhulima et al, 2020). pH yang cocok bagi pertumbuhan teripang yaitu 6,50-7,50 untuk perairan produktif dan 7,50-8,50 untuk perairan sangat produktif.…”
Section: Kelangsungan Hidupunclassified
“…Hartati et al (2019) telah melakukan kajian awal populasi H. atra di P. Panjang, namun belum mengkaji hubungan panjang dan beratnya. Penelitian hubungan panjang berat telah dilakukan terhadap teripang di perairan Tanjung tiram, Konawe Selatan, Sulawesi Tenggara (Kaenda et al, 2016), H. scabra di Teluk Un, Maluku Tenggara (Natan et al, 2015), Perairan Maluku Tengah (Manuputty, 2019), H. atra di beberapa perairan Taman Nasional Karimunjawa (Panuluh et al, 2019) dan H. scabra, H. atra dan Bohadchia marmorata (Luhulima et al, 2020) di Maluku.…”
Section: Pendahuluanunclassified